2022
DOI: 10.1167/iovs.63.6.15
|View full text |Cite
|
Sign up to set email alerts
|

Axial Length Distributions in Patients With Genetically Confirmed Inherited Retinal Diseases

Abstract: Purpose We investigated axial length (AL) distributions in inherited retinal diseases (IRDs), comparing them with reference cohorts. Methods AL measurements from IRD natural history study participants were included and compared with reference cohorts (TwinsUK, Raine Study Gen2-20, and published studies). Comparing with the Raine Study cohort, formal odds ratios (ORs) for AL ≥ 26 mm or AL ≤ 22 mm were derived for each IRD (Firth's logistic regression model, adjusted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The proband in this study, in addition to the typical clinical phenotypes of OA1, was also complicated with high myopia. It has been found from some studies that, unlike the TYR gene-related albinism, GPR143 gene-related albinism is more likely to be complicated with a short ocular axis [ 44 ]. In 2022, Pavan Verkicharla analyzed the refractive status of 618 albinos and found that high myopia being much more prevalent than hyperopia [ 45 ], suggesting that high myopia is also a common sign in albinism, and that if patients are complicated with high myopia, then, as in this case, albinism-like fundus changes are often less typical, so that OA1 is often misdiagnosed as idiopathic congenital nystagmus [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proband in this study, in addition to the typical clinical phenotypes of OA1, was also complicated with high myopia. It has been found from some studies that, unlike the TYR gene-related albinism, GPR143 gene-related albinism is more likely to be complicated with a short ocular axis [ 44 ]. In 2022, Pavan Verkicharla analyzed the refractive status of 618 albinos and found that high myopia being much more prevalent than hyperopia [ 45 ], suggesting that high myopia is also a common sign in albinism, and that if patients are complicated with high myopia, then, as in this case, albinism-like fundus changes are often less typical, so that OA1 is often misdiagnosed as idiopathic congenital nystagmus [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…106 Refractive error also provides clues to inherited retinal disorders and underlying genetic aetiology. 107 Myopia maybe the only ocular feature or part of a more complex ocular or clinical phenotype. 108 Genetic tests have the potential to not only enhance diagnostic precision but also provide targets for cutting edge genetic therapies.…”
Section: Geneticsmentioning
confidence: 99%
“…Refractive error also provides clues to inherited retinal disorders and underlying genetic aetiology 107 . Myopia maybe the only ocular feature or part of a more complex ocular or systemic clinical phenotype 108 …”
Section: Geneticsmentioning
confidence: 99%
“… 23 , 48 An analysis of a large group of genetically characterized patients with inherited retinal disease has demonstrated that four genetic subtypes, blue cone monochromacy, Bornholm eye disease (both associated with OPN1LW and OPN1MW or their regulatory regions), and retinal dystrophies caused by RPGR and RPE65 mutations were associated with increased axial length. 49 Two genes associated with albinism (such as OCA2 and TYR ) also increased the risk of longer axial length. Short axial lengths are also seen in certain gene variants.…”
Section: Etiology Of High Myopia In Childrenmentioning
confidence: 99%